2013
DOI: 10.1021/ja309404j
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-alkyltellurophene)s Are Solution-Processable Polyheterocycles

Abstract: The synthesis and characterization of a series of poly(3-alkyltellurophene)s are described. Polymers are prepared by both electrochemical and Kumada catalyst transfer polymerization methods. These polymers have reasonably high molecular weights (M(n) = 5.4-11.3 kDa) and can be processed in a manner analogous to that of their lighter atom analogues. All examples exhibit red-shifted optical absorption, as well as solid-state organization, as evidenced by absorption spectroscopy and atomic force microscopy. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 49 publications
3
118
0
Order By: Relevance
“…Time‐dependent density functional theory (TD‐DFT) simulations were performed to gain insight into the absorption behavior (see the Supporting Information). Simulations of individual chalcogenophene rings predicted absorption bands at increasing wavelengths moving from thiophene, to selenophene, to tellurophene, in agreement with previous reports . Simulations of monomer units showed an absorption band at 340 nm, red‐shifting upon switching to longer units (dimer and trimer).…”
Section: Resultssupporting
confidence: 88%
“…Time‐dependent density functional theory (TD‐DFT) simulations were performed to gain insight into the absorption behavior (see the Supporting Information). Simulations of individual chalcogenophene rings predicted absorption bands at increasing wavelengths moving from thiophene, to selenophene, to tellurophene, in agreement with previous reports . Simulations of monomer units showed an absorption band at 340 nm, red‐shifting upon switching to longer units (dimer and trimer).…”
Section: Resultssupporting
confidence: 88%
“…Route A reported that gaseous buta-1,3diyne was synthesized by treatment of 1,4-dichloroacetlynene with KOH, and then was directly transferred to another system to react with Na 2 Te in-situ, affording tellurophene T1 with ca. [15] Bendikov et al developed a new strategy to synthesize tellurophene-based small molecule T3 as shown in Route B. [13] Although the synthesis of tellurophene-containing conjugated systems is challenging, several groups have made important progress in this field.…”
Section: Ring Closure Of Tellurophenementioning
confidence: 99%
“…[ 58 ] The synthesis of regioregular poly(3-alkylselenophenes) (P3ASe) [ 59,60 ] and poly(3-alkyltellurophenes) [ 61 ] by the Grignard metathesis (GRIM) polymerization route has recently been accomplished, thereby expanding the range of semicrystalline, π-conjugated polymers available. Polyselenophenes exhibit significantly different crystallization and optoelectronic properties to those known for P3HT such as a lower band gap (by ca.…”
Section: Introductionmentioning
confidence: 99%